Moderately severe acute pancreatitis after snake bite: a case report from Southern China - Cao, Ronglai; He, Jinli; Yu, Zhengping; Chen, Youxiang; Zhu, Liang (Zeitschrift für Gastroenterologie, 2023)
Venomous snakebites are not rare worldwide, and this is also the situation in the mountainous regions of southern China, where they pose a serious health risk to the local population. Snake venom usually causes a variety of clinical symptoms, such as local pain and swelling, systemic coagulation system abnormalities, and shock, but rarely leads to acute pancreatitis. In this report, we presented a rare case of moderately severe acute pancreatitis caused by snake venom even after prompt antivenom treatment. The patient was relieved, obviously, with effective treatment of acute pancreatitis and was discharged without severe complications. Although acute pancreatitis after snake bite is a rarity, its serious complications and lethality still deserve our utmost attention, and timely and standardized treatment of acute pancreatitis is needed in addition to antivenom treatment.
Keywords: snakebites; venom; acute pancreatitis; case report